The Role Of Community In Education On Prevention Of Sexually Transmitted Diseases - Abdul Gafur; Eka Apriyanti; Mohammad Ahsan S Mandra (International Journal of Ethno-Sciences and Education Research, 2026)
Sexually transmitted diseases (STDs), particularly HIV/AIDS, continue to pose a major public health challenge among at-risk populations such as men who have sex with men (MSM) and transgender individuals (TG). These groups experience heightened vulnerability due to social stigma, discrimination, and limited access to inclusive health education, which often undermines prevention efforts. Population education plays a strategic role in addressing these barriers by improving knowledge, shaping attitudes, and encouraging preventive behaviors through participatory and community-based approaches. This study aims to analyze the role of population education in enhancing awareness and strengthening sexually transmitted infection (STI) prevention among at-risk groups in Parepare City, Indonesia. This study employed a qualitative descriptive design to explore participants’ experiences and community dynamics. Data were collected through participant observation, thematic dialogues, group discussions, and documentation of educational activities. The findings reveal that population education delivered through interactive strategies such as community dialogues, educational drama, public campaigns, and integration with local health services successfully increased community participation and engagement. These approaches contributed to improved awareness of HIV/AIDS prevention, greater utilization of information and communication technology for health information, and the internalization of anti-stigma and non-discriminatory values. However, implementation challenges were identified, particularly weather-related factors that affected participant attendance and activity scheduling. Overall, the study concludes that community-based population education represents an effective promotive and preventive strategy for STI prevention among at-risk populations and has strong potential to support inclusive and sustainable public health interventions at the local level.